Causes of Water Logging in Jhajjar District: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Water logging is main problem in areas where rice cultivation is increasing ground water is saline. In these areas the ground water is not being used and water from other far areas is being brought by pipelines and irrigation in mostly done by canal water. Due to sore water the pores of land are blocked and water logging starts in these types of areas. Using of excess of fertilizers also helps in increasing water logging.